Effect of Aquatic, Alcoholic and Oily Extracts of Cocos nucifera L.on the Growth of Certain Pathogenic Bacteria Isolated from Wounds and Burns Infections (Baghdad Science Journal, 2012)
Three types of extracts ( aquatic, alcoholic, and oily ) were prepared from the fruits of coconuts, and a series of chemical tests were conducted in addition to the use of the FTIR equipment to determine the active locations in the prepared extracts. The results indicated the presence of active compounds (tannins, saponins, flavonoids, turbines and steroids) in the extracts prepared from the fruits of coconuts, also the antimicrobial capability of these extracts were tested on pathogenic bacteria isolated from wounds and burns infections cases. The results proved that the concentration 80 mg/ml of the aquatic extract is the minimum inhibitory concentration for the microbes: Proteus vulgaris and Pseudomonas fluorescence, while the concentration of 160 mg/ml is the lethal concentration for them, as for the alcoholic extract the concentration of 4 mg/ml was the minimum inhibitory concentration for these two microbes , while the concentration of 32 mg/ml was the lethal concentration to them, as for the oily extract the two concentrations of 1:1 and 1:3 were the minimum inhibitory concentration and the lethal concentration respectively for these two microbes, while for the Burkhorderia mallei microbe the concentrations of 40, 4, 6,2:1 of the aquatic, alcoholic and oily extracts respectively were the minimum inhibitory concentrations for their growth, while the concentrations 160,32,3:1 of the aquatic, alcohol and oily extract respectively the lethal concentrations to them.